2005
DOI: 10.1016/j.geoderma.2004.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Trace element accumulation in Mn—Fe—oxide nodules of a planosolic horizon

Abstract: The aim of this work was to determine the importance of nodule formation on the dynamics of major and trace elements (TEs) along a Planosol toposequence developed in metamorphic parent material at La Châtre (Massif Central, France). The different horizons were sampled within three pits and analysed for major and trace element contents. The nodule-rich horizon was studied more closely. A simplified sequential extraction scheme, X-ray diffraction (XRD) and microscopic approaches were used in order to determine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 20 publications
2
55
0
Order By: Relevance
“…1b). The gravelly and concretion-rich horizon below comprises concretions which are mainly composed of several types of cements (Fe-rich, Si-and Al-rich, Mn-rich and Ti-rich) surrounding grains of quartz, feldspars, micas and accessory minerals (Salvador-Blanes, 2002;Cornu et al, 2005) …”
mentioning
confidence: 99%
“…1b). The gravelly and concretion-rich horizon below comprises concretions which are mainly composed of several types of cements (Fe-rich, Si-and Al-rich, Mn-rich and Ti-rich) surrounding grains of quartz, feldspars, micas and accessory minerals (Salvador-Blanes, 2002;Cornu et al, 2005) …”
mentioning
confidence: 99%
“…Lead Childs (1975) and Rankin and Childs (1987) pointed to higher concentrations of Pb in FMCs than in the corresponding surrounding soil materials. Cornu et al (2005) found that accumulation of Pb in the ferromanganese nodules was due to the high specific adsorption of Pb by the Mn oxides. In contrast, Palumbo et al (2001) reported that Pb appeared to be associated with the Fe-rich phase…”
Section: Trace Element Partitioning With Mn-fe Phases In Fmcsmentioning
confidence: 98%
“…Mn and Fe are important elements for plant and animal nutrition (Liu et al, 2002). In addition, oxides and/or hydroxides of both Mn and Fe are the main Mn-Fe phases in the soils, and they often act as strong scavengers of trace elements during weathering and pedogenesis (Burns, 1976;McKenzie, 1980;Bellanca et et al, 1985;Latrille et al, 2001;Liu et al, 2002;Cornu et al, 2005), few have focused on the distribution of trace elements in FMCs at different depths in the soil profile (Feng, 2010(Feng, , 2011. There is also a lack of information both on the direct quantitative relationship between MnFe phases and trace elements, and on the comparative capacities of the Mn-and Fe-phases to retain trace elements in FMCs at different depths and in various pedoenvironments (Chao and Theobald, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…This fraction is primarily expected to dissolve soil iron oxides, and the high affinity of trace metal to these phases in soils is a well-known phenomenon (e.g. Cornu et al 2005). Both metals show similar reducible ratios for both soil groups: 7.7 ± 6.8% and 10.5 ± 10.2% for Cu, and 28.9 ± 12.4% and 29.9 ± 9.6% for Pb in the Luvisols and non-Luvisols, respectively.…”
Section: Central European Geology 57 2014mentioning
confidence: 99%
“…On the other hand, both Cu and Pb were also found to be of high affinity to soil iron oxides. However, Cornu et al (2005) found that metals forming stable hydroxide and carbonate complexes are preferentially bound to the (slightly) positively charged iron oxide surfaces. As Pb is much more able to form such complexes (hydroxide complexes in the acid Luvisol and carbonate ones in the alkaline non-Luvisol environments) than Cu, its higher affinity to iron oxides in the studied soils is expected.…”
Section: Central European Geology 57 2014 Distribution Geochemical mentioning
confidence: 99%